2007
DOI: 10.1002/anie.200605078
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerizable Heterodienes Derived from a Phosphine Borane

Abstract: Stable relations: Reaction of phenylazide with a phosphine borane derivative gives rise to an intramolecularly stabilized phosphazide 1 (R=iPr, R′=mesityl) that undergoes an unprecedented photoisomerization process associated with a change from an Nα→B to an Nβ→B interaction (see scheme). The generality and possible reversibility of such phenomena are demonstrated with the related phosphazine adduct 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
43
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 37 publications
1
43
0
4
Order By: Relevance
“…[12] Related is the reactivity of frustrated Lewis pairs (FLPs) [13] towards organic azides, buti nt his case multiple Staudinger intermediates have been isolated. Phosphorus/boron-based FLPs have been shown to add to the a-nitrogen of the azide form-ing coordinationm ode D (Figure 1) [14] and, in one case, it was found that upon irradiation this speciesr earranges to a,b-nitrogen adduct E. [15] The a,g-nitrogen coordinationm ode F was found by treatingageminal FLP with mesityl azide. [16,17] In analogy to the reactivityo fN HCs (C;F igure 1), dinitrogen elimination occurs when TMS azide was reacted with aP /Al-based FLP affording heterocycle G, [18] yet in this case no follow-up chemistry has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Related is the reactivity of frustrated Lewis pairs (FLPs) [13] towards organic azides, buti nt his case multiple Staudinger intermediates have been isolated. Phosphorus/boron-based FLPs have been shown to add to the a-nitrogen of the azide form-ing coordinationm ode D (Figure 1) [14] and, in one case, it was found that upon irradiation this speciesr earranges to a,b-nitrogen adduct E. [15] The a,g-nitrogen coordinationm ode F was found by treatingageminal FLP with mesityl azide. [16,17] In analogy to the reactivityo fN HCs (C;F igure 1), dinitrogen elimination occurs when TMS azide was reacted with aP /Al-based FLP affording heterocycle G, [18] yet in this case no follow-up chemistry has been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the s ‐ cis conformation can be destabilized by sterically demanding substituents. Other strategies are the incorporation of the phosphazide into a cyclic4 or macrocyclic5 system, or its coordination to metal atoms like boron,6 zirconium,7 molybdenum,8 tungsten,9 iron,10 ruthenium,11 cerium,12 or lutetium13 in which different coordination modes have been found. In a few cases, open‐chain phosphazides in an s ‐ cis conformation with CH 2 CN,14 adamantyl,15 or ortho ‐ closo ‐dicarbadodecaboranyl16 substituents at the γ‐nitrogen atom were observed.…”
Section: Introductionmentioning
confidence: 99%
“…Both reagents gave persistent adducts with the Al FLP 1 but relatively long PÀC distances to the carbonyl Catoms and adynamic behavior of the benzaldehyde adduct in solution confirmed relatively weak P À Ci nteractions. [3] Thel ower polarization of the C = O bonds by Ga results in al ess positively charged Ca tom and prevents the formation of isolatable adducts of 3.T his behavior may be important for activation processes,w hich are hindered by the formation of stable complexes.Anormal FLP reaction [1,13] was found for an azide (5;S cheme 2, Figure 2). [10] Thet erminal Na tom was coordinated to Pa nd Ga to form aGaCPN heterocycle with an exocyclicN 3 group.…”
mentioning
confidence: 96%